Ca2+/TEMPO dual-modified bacterial nanocellulose interfaces for programmable Pickering emulsions and controlled curcumin release - Nan Zhang; Xueyan Gao; Yu Zhang; Yonghao Li; Xuan Hu; Lingfei Li; Wei Liu (Food Hydrocolloids, 2026)

A visible yellow trivalent chromium conversion coating modified by tannic acid on 7075 aluminum alloy - Jiantao Qi; Yonghao Liu; Yu Wang; Yaowei Wang; Hao Ren; Wen Zhu; Sungmo Moon (Chemical Engineering Journal, 2026)

Development and property characterization of sustainable microalgal graphene-like carbon - Zhifei Yu; Lu Li; Aonan Wei; Yonghao Zhao (Bioresource Technology, 2026)

Pharmaceuticals and personal care products in China’s aquatic environments: A decadal update (2013–2022) - Guosong Chang; Yonghao Huangfu; Yue Shi; Xinyue Shi; Shuai Cao; Yiting Ge; Ke An; Qingwei Bu; Gang Yu (Journal of Hazardous Materials, 2026)

Multimodal detection and analysis of microplastics in human clear cell renal cell carcinoma - Kenan Zhang; Shuanbao Yu; Shixu Chen; Zhenzhen Zhou; Yonghao Zhan; Xuepei Zhang (Environmental Pollution, 2025)

Oxytocin Regulated Neuroinflammation through OTR/Mitochondria Mediated Pathway to Improve Hypoxia-Induced Brain Injury - Xiaomei Yang; Kai Li; Lin Chen; Lei Wang; Xuyang Wang; Kangping Lu; Yu Bai; Yonghao Hou; Jingchen Hou; Chao Wang; Xiaoyan Cheng; Joseph Oldam; et al. (Molecular Neurobiology, 2025)

In-situ atmospheric thermoelectric conversion on Mars - Yuzhuo Yang; Yonghao Zhang; Yu Yao; Gang Pei; Hua Tian; Lingfeng Shi; Gequn Shu (Science Bulletin, 2025)

Improving the efficiency of a CO2 heat pump for simultaneous heating and cooling coupled with an ambient source - Zhaoyang Yuan; Jintao He; Yonghao Zhang; Yu Yao; Hua Tian; Lingfeng Shi; Gequn Shu (International Journal of Refrigeration, 2025)

A hybrid cooling and power cogeneration scheme for broadening adaptability to distributed buildings: conceptual design, modeling, and operational assessment - Yonghao Zhang; Lingfeng Shi; Hua Tian; Jintao He; Yu Yao; Gequn Shu (Energy and Buildings, 2025)

Preoperative Sleep Deprivation Exacerbates Anesthesia/Surgery-induced Abnormal GABAergic Neurotransmission and Neuronal Damage in the Hippocampus in Aged Mice - Yun Li; Siwen Long; Jiafeng Yu; Jingyu Feng; Shuqi Meng; Yize Li; Lina Zhao; Yonghao Yu (Molecular Neurobiology, 2025)

Engineering cellulosic paper into a bending strain sensor using chemical additives: Metal salt-based treatment and ethanol-assisted processing - Jianmin Peng; Xin Fu; Xiaoyan Yu; Zhongfei Yuan; Xueren Qian; Yonghao Ni; Zhibin He; Jing Shen (Carbohydrate Polymers, 2025)

A novel strategy for preparing gradient hydrogels based on density difference-driven bidirectional self-growth - Yu Yang; Weikun Jiang; Honglei Chen; Fangong Kong; Shubin Wu; Yonghao Ni; Yu Liu (Chemical Engineering Journal, 2025)

Dominant defect and microstructure transformation engineering for highly efficient low-bandgap stannite solar cells - Zixuan Yu; Shuoren Li; Chuanhao Li; Sihao Huang; Yonghao Wang; Zhenghua Su; Guangxing Liang; Chang Yan (Chemical Engineering Journal, 2025)

Environmental enrichment attenuates sevoflurane anesthesia-induced learning deficits in aged mice through regulating TTBK1 and phosphorylated Tau expression - Xuenan Chang; Xiaoli Zhuang; Jingyu Feng; Yonghao Yu; Yang Yu (Experimental Brain Research, 2025)

Atomic H*-mediated electrochemical reduction of bromate by a facile Ti/Pd@MXene filter electrode - Xu Yin; Jiatian Yu; Zhifeng Gao; Wei Li; Kajia Wei; Yun Jiang; Yonghao Zhang; Haoming Chen; Weiqing Han (Journal of Hazardous Materials, 2025)

Preparation of Al-5Li@FSG powders through fluorination-energetic modification to improve the comprehensive performance of alloy powders - Haiyang Wang; Shuo Wang; Xuanyan Liu; Youqi Zhu; Tinglu Song; Haiyue Yu; Hongdi Fu; Kangcheng Xu; Huaqiang Zhu; Yonghao Zhao; Siyuan Tang; Meishuai Zou (Chemical Engineering Journal, 2025)

Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Yuxin Wu; Yiran Lin; Bing Lin; Yukun Huang; Zhide Yu; Yonghao Ma; Yuwei Feng; Qiaoyi Chen; Along Gao; Hu Shu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides , we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism, and the serum glucose content and lactate dehydrogenase activity were significantly upregulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in the liver, and mRNA expression of three genes (i.e., LDHA , GLUT1 , and MCT2 ) also showed a high expression trend. In serum, three immune-related enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IL-8 , IFNγ , MyD88 , and NF-kB ) were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53 , Bax , Bcl-2 , and Caspase-9 ) was closely related to the degree of apoptosis in the liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO, 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.

Metformin promotes the survival of random skin flaps via the activation of Nrf2/HO-1 signaling - Yan Chen; Ruxin Cheng; Wenyan Lu; Yonghao Fan; Ye Yu; Ling Huang; Zhenling Wan; Shaojiang Zheng (Chemico-Biological Interactions, 2024)

The Role of KDM2A and H3K36me2 Demethylation in Modulating MAPK Signaling During Neurodevelopment - Zongyao Ren; Haiyan Tang; Wendiao Zhang; Minghui Guo; Jingjie Cui; Hua Wang; Bin Xie; Jing Yu; Yonghao Chen; Ming Zhang; Cong Han; Tianyao Chu; et al. (Neuroscience Bulletin, 2024)

A review of vision-based crop row detection method: Focusing on field ground autonomous navigation operations - Shuo Zhang; Yu Liu; Kun Xiong; Yonghao Tian; Yuefeng Du; Zhongxiang Zhu; Mingwei Du; Zhiqiang Zhai (Computers and Electronics in Agriculture, 2024)

Two-way predation between larvae of Spodoptera frugiperda and Spodoptera litura - Yuxue Wang; Natasha Isabel Tanatsiwa Mbiza; Yonghao Yu; Haoran Zhang; Zongwei Hu; Ting Liu; Yi Wang; Yi Zhang; Xincheng Luo; Longyan Chu; Yazhen Yang; Xiangping Wang; et al. (Journal of Asia-Pacific Entomology, 2024)

Anthracene degradation involved by antibiotic biosynthesis monooxygenase (ABM) in Comamonas testosteroni - Miao Xu; Yonghao Liu; Hui Li; Xiao Yang; Weijie Yue; Yu Zhang; Dong Liu; Ming Wu; Dan Wang; Guangming Xiong; Liquan Guo; Kai Song (International Biodeterioration & Biodegradation, 2024)

Glacial debris flow susceptibility mapping based on combined models in the Parlung Tsangpo Basin, China - Yonghao Zhou; Xiewen Hu; Chuanjie Xi; Hong Wen; Xichao Cao; Tao Jin; Ruichen Zhou; Yu Zhang; Xueqiang Gong (Journal of Mountain Science, 2024)

The cross-linking ability of dialdo-galactose in food processing condition - Yonghao Liu; Jiaqi Yu; Honghua Cao; Changhu Xue; Kai Chen; Ying Xu; Xun Sun (Food Chemistry, 2024)

Revealing the specificity of map method to predict the performance of a combined cooling and power cycle under operating conditions - Yu Yao; Lingfeng Shi; Jintao He; Xiaocun Sun; Bowen Lu; Yonghao Zhang; Hua Tian; Xuan Wang; Gequn Shu (Journal of Cleaner Production, 2023)

Impacts of replacing dietary fish meal with poultry by-product meal on growth, digestive enzymes and gut microbiota, biomarkers of metabolic and immune response, and resistance to Vibrio challenge in abalone (Haliotis discus hannai) - Zhenhua Wu; Xiaojun Yu; Yonghao Fu; Jinshu Guo; Mingzhu Pan; Yanlin Guo; Jiahuan Liu; Kangsen Mai; Wenbing Zhang (Aquaculture, 2023)

In-situ decoration of Cu2(OH)3F on BiOBr with exposed (010) facets: Heterojunctions and photo-Fenton-like synergistic promote Cu+/Cu2+ circulation - Yaxin Guo; Yonggang Liu; Shiduo Hao; Xueying Zhang; Yonghao Yu (Journal of Water Process Engineering, 2023)

Distribution and relationship of antibiotics, heavy metals and resistance genes in the upstream of Hanjiang River Basin in Shiyan, China - Jing Li; Lijuan Li; Qin Li; Wen Fang; Yonghao Sun; Yu Lu; Jing Wang; Yanrong Zhu; Yao Zhang (Environmental Geochemistry and Health, 2023)

Low-coordinated Co-N3 sites induce peroxymonosulfate activation for norfloxacin degradation via high-valent cobalt-oxo species and electron transfer - Caiyun Wang; Xiaoxia Wang; Hu Wang; Lijie Zhang; Yonghao Wang; Chung-Li Dong; Yu-Cheng Huang; Peng Guo; Rongsheng Cai; Sarah J. Haigh; Xianfeng Yang; Yuanyuan Sun; et al. (Journal of Hazardous Materials, 2023)

Energy-efficient reuse of bio-treated textile wastewater by a porous-structure electrochemical PbO2 filter: Performance and mechanism - Yonghao Zhang; Liankai Gu; Ying Zhang; Jing Yang; Qian Li; Shuyan Yu; Congju Li; Kajia Wei (Environmental Research, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Residential greenness, air pollution and incident neurodegenerative disease: A cohort study in China - Zhanghang Zhu; Zongming Yang; Luhua Yu; Lisha Xu; Yonghao Wu; Xinhan Zhang; Peng Shen; Hongbo Lin; Liming Shui; Mengling Tang; Mingjuan Jin; Jianbing Wang; et al. (Science of The Total Environment, 2023)

Zinc-ion engineered Plant-based multifunctional hydrogels for flexible wearable strain Sensors, Bio-electrodes and Zinc-ion hybrid capacitors - Yang Wang; Weikun Jiang; Jiao Li; Md Sohel Ahommed; Chao Wang; Xingxiang Ji; Yu Liu; Guihua Yang; Yonghao Ni; Gaojin Lyu (Chemical Engineering Journal, 2023)

An optimization strategy for photo-Fenton-like catalysts: Based on crystal plane engineering of BiVO4 and electron transfer properties of 0D CQDs - Xueying Zhang; Yonggang Liu; Yunpu Zhai; Yonghao Yu; Yaxin Guo; Shiduo Hao (Environmental Research, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Efficient electron transfer and copper species transformation under the synergy of BiVO4 and novel Cu2(OH)3F nanosheets - Xueying Zhang; Yonggang Liu; Yonghao Yu; Lifen Wang; Yinjun Lin (Environmental Science and Pollution Research, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Ferroptosis is involved in the development of neuropathic pain and allodynia - Huixing Wang; Xiaodong Huo; Chenyang Han; Jiang Ning; Hongguang Chen; Bo Li; Jingzhi Liu; Wenting Ma; Quanbo Li; Yonghao Yu; Kemei Shi (Molecular and Cellular Biochemistry, 2021)

Hydrogen alleviates cell damage and acute lung injury in sepsis via PINK1/Parkin-mediated mitophagy - Hongguang Chen; Huaying Lin; Beibei Dong; Yaoqi Wang; Yonghao Yu; Keliang Xie (Inflammation Research, 2021)

Genome-Wide Identification and Expression Analysis of Heavy Metal Stress–Responsive Metallothionein Family Genes in Nicotiana tabacum - Qin Yu; Linshen He; Chunsong Huo; Xiaohan Jiang; Hua Chen; Run Wang; Minzhi Tang; Ling Dong; Ji Chen; Yonghao Li; Shunqin Zhu; Wanhong Liu (Plant Molecular Biology Reporter, 2021)

A Role for Transmembrane Protein 16C/Slack Impairment in Excitatory Nociceptive Synaptic Plasticity in the Pathogenesis of Remifentanil-induced Hyperalgesia in Rats - Yize Li; Linlin Zhang; Jing Li; Chunyan Wang; Yi Chen; Yuan Yuan; Keliang Xie; Guolin Wang; Yonghao Yu (Neuroscience Bulletin, 2021)

Molecular hydrogen alleviates brain injury and cognitive impairment in a chronic sequelae model of murine polymicrobial sepsis - Yi Jiang; Kai Zhang; Yang Yu; Yaoqi Wang; Naqi Lian; Keliang Xie; Yonghao Yu (Experimental Brain Research, 2020)

Shadow detection in SAR images based on greyscale distribution, a saliency model, and geometrical matching - Haixiang Li; Xuelian Yu; Yonghao Tang; Xuegang Wang (International Journal of Remote Sensing, 2020)

Hydrogen attenuates sepsis-associated encephalopathy by NRF2 mediated NLRP3 pathway inactivation - Keliang Xie; Yang Zhang; Yaoqi Wang; Xiaoyin Meng; Yuzun Wang; Yonghao Yu; Hongguang Chen (Inflammation Research, 2020)

First record of a damage to potato caused by Schrankia costaestrigalis (Stephens, 1834), a new potential pest in China - Xianru Zeng; Yonghao Yu; Xuyuan Gao; Xiuzhen Long; Xiaodong Jiang; Jimin Liu; Dewei Wei; Yulin Gao; Zhongshi Zhou (Journal of Pest Science, 2020)

Effects of a novel curcumin derivative on the functions of kidney in streptozotocin-induced type 2 diabetic rats - Xuegu Xu; Yonghao Cai; Yinfei Yu (Inflammopharmacology, 2018)

Critical role of connexin43 in zebrafish late primitive and definitive hematopoiesis - Qiu Jiang; Dong Liu; Shuna Sun; Jingying Hu; Li Tan; Yuexiang Wang; Yonghao Gui; Min Yu; Houyan Song (Fish Physiology and Biochemistry, 2010)